The diagnostic accuracy to Technetium 99m labelled erythrocyte scintigraphy in the investigation of hepatic mass lesions : special reference to hepatic cavernous haemangioma and hepatocellular carcinoma - Lourens, Steven (Division of Nuclear Medicine, 2018)
The distinction between cavernous haemangiomas of the liver (which are the second most common hepatic mass lesions) from malignant lesions, is often difficult. An incorrect diagnosis of cavernous haemangioma, in a patient with malignancy, may adversely influence the outcome of subsequent treatment in these patients, due to delay in therapy. Although previous studies have suggested that ⁹⁹ᵐTc erythrocyte blood pool scintigraphy is both highly sensitive and specific for haemangiomas, a basic flaw in all previous studies has been the small number of control patients studied. Bayesian analysis clearly shows that specificity for a test is dependant on the pre-test probability of the lesion being present. Thus all the studies done to date, may reflect an inappropriately high specificity for ⁹⁹ᵐTc scintigraphy, in diagnosing cavernous haemangiomas, because they have mainly studied patients with haemangiomas and relatively few patients with other lesions. This study was thus undertaken to clarify the true accuracy of this technique, in distinguishing haemangiomas from other hepatic mass lesions, by studying a large number of patients with haemangiomas and other hepatic mass lesions.